Trends in Earnings Inequality and Earnings Instability among U.S. Couples: How Important Is Assortative Matching? - Dmytro Hryshko; Chinhui Juhn; Kristin McCue (Institute for the Study of Labor (IZA), 2014)
We examine changes in inequality and instability of the combined earnings of married couples over the 1980-2009 period using two U.S. panel data sets: Social Security earnings data matched to Survey of Income and Program Participation panels (SIPP-SSA) and the Panel Study of Income Dynamics. Relative to male earnings inequality, the inequality of couples' earnings is both lower in levels and rises by a smaller amount. We also find that couples' earnings instability is lower in levels compared to male earnings instability and actually declines in the SIPP-SSA data. While wives' earnings played an important role in dampening the rise in inequality and year-to-year variation in resources at the family level, we find that marital sorting and coordination of labor supply decisions at the family level played a minor role. Comparing actual couples to randomly paired simulated couples, we find very similar trends in earnings inequality and instability.
Keywords: J1; J2; J3; 330; inequality; instability; matching